PENGARUH KEPUTUSAN KONSUMEN DALAM MEMBELI RUMAH DITINJAU DARI HARGA, LOKASI DAN PENDAPATAN - Retno Dewi Wijiastuti; Yohanes Helfianus Mas Bria (ICMA Nasional, 2023)
The high level of population density causes the need for residential houses to also increase. The aim of this research is to find out what factors influence consumers decisions in buying a house, in terms of price, location and income. This research uses primary data by distributing questionnaires to 90 people who have bought a house at KPR Putra Resident Malibela, Sorong City. This research uses multiple linear regression analysis with the SPSS version 20 application program. Meanwhile, the approach used in this research is quantitative and correlation methods. The results of the research show that price, location and income partially influence consumer decisions in buying a house. It is hoped that this research can become a basic reference or consideration for housing developers in determining the right marketing strategy or business strategy so that it can meet the needs, tastes and desires of consumers